Clinical neuropsychology : behavioral and brain science - Bradshaw, John L., 1940- (Academic Press, 1995)
Clinical Neuropsychology is an up-to-the minute overview of the major and many interesting minor disorders and behavioral syndromes caused by localized brain damage or abnormal brain functioning. The text combines clinical findings with studies on normal, healthy individuals to provide a comprehensive picture of the human brain's operation and function. Biological rather than cognitive in emphasis, Clinical Neuropsychology integrates findings across a broad range of disciplines. This text serves as an up-to-date reference source for clinicians, researchers, and graduate students and as a textbook for advanced undergraduate courses on clinical neuropsychology. Coverage includes the ramifications of localized brain damage/abnormal brain functioning on emotion, thought, language, and behavior, illustrative case histories, chapter overviews, and more than 700 recent references.